The historical dimension of the “Bimaristan” Islamic hospital work system From the 1st to the 7th century AH - al-Sharif, Umm al-Izz Abdul Qadir Muhammad (Tobruk University Journal of Social and Human Sciences, 2022)
During the historical period from the first to the seventh century AH, the Arab and Islamic countries witnessed the existence of a residential health system called "Bimaristan", which began to develop in its architectural form from one era to another according to the ruling political authority that held the reins of government in the Arab Islamic countries, whether in the countries of the Hajjar or In Iraq, or in the Levant, and according to the scientific and medical skills that came to the Arab and Islamic schools. In this research, pivotal points related to the subject of the study will be discussed, including: The Bimaristan system during the first Arab Islamic state - the era of the Prophet - may God bless him and grant him peace (1-11 AH/622-632AD). ;The Bimaristan System in the Rashidun Era (11-41 AH / 632-661 AD) The Bimaristan system during the early Umayyad dynasty (41-132 AH / 661-749 AD). The Bimaristan system during the Abbasid state (132-656 AH / 749-1258 AD).